Evaluasi Pelayanan Perbankan Syariah Di Era Digitalisasi Studi Kasus Bank Jatim Syariah Cabang Pasuruan - Nia Maulidia; Sagita Martha Triyani; Irham Maulana (Cashless : Journal of Sharia Finance and Banking, 2023)
The rapid growth of Bank Jatim Pasuruan's digitalization, as shown by the increasing growth of its Assets, and Financing, from year to year, shows how competitive and universal the sharia system has been applied to services in the era of digitalization. It also shows that the governance carried out by management is carried out professionally, trustfully and very well. Of course, this is also inseparable from the factors that influence it. This study aims to analyze the factors that influence the service supporters of the digitalization era and service inhibiting factors, and see the causality relationship between the variables tested, the magnitude of each influence, and the response given, in this study, researchers used several methods. This method is done to get data from the field directly so that the data obtained can be trusted and accounted for. The variables that will be tested in this study are digitalization, services.